If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2y = 15 Solving 12 + -2y = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2y = 15 + -12 Combine like terms: 12 + -12 = 0 0 + -2y = 15 + -12 -2y = 15 + -12 Combine like terms: 15 + -12 = 3 -2y = 3 Divide each side by '-2'. y = -1.5 Simplifying y = -1.5
| 22=9+5y | | -2(2t+5)=2 | | 4(f-6)=-32 | | f(x)=7x^2+14x+1 | | 10(s-4)=-98 | | -c(-8)=5 | | -22=14-9b | | 5+7=-5 | | 5+7=-6 | | (e+3)*3=12 | | sqrtx=(235/100) | | (q-3)*5=40 | | (u-8)*7=56 | | 8=-4r | | u/9=5 | | -40=-8u | | (X)(2x-1)=66 | | 6x^2-12x-108= | | 27a^5b^3+64a^8= | | (x)(0.75)+(1.0234-x)(0.75)=0.6635 | | 276x^2+0.94*x-0.055=0 | | 18=9r | | -9=9w | | 2=2u | | 18=-3s | | b^2+2b-76=0 | | 9(4x-6)=40 | | 2/5-z=10.4 | | (x^2.x^-5.x^3)/x^4 | | 25x=5x-15 | | n+-9=-9 | | 5x-2x+4=3x+3+x-1 |